Internationalisation des élites académiques suisses au XXe siècle : convergences et contrastes - Thierry Rossier (Cahiers de la Recherche sur l'Education et les Savoirs, 2015)
Resting on a new database on professors of law and economic sciences from Swiss universities in the 20th century, this article accounts for different dynamics of internationalisation of this elite group. Three major conclusions can be drawn from our analyses: first, we can divide the 20th century in three distinct historic periods. A strong internationalisation of the academic elites at the beginning of the century is followed by a period of nationalisation or regionalisation subsequent to the First World War. From the 1960s onwards, we observe a “re-internationalisation”, which is even accelerated in the 1980s. Second, professors in the economic sciences are more international and less locally anchored than their counterparts in law, in particular when we examine their nationality or their place of education. Finally, the German preponderance among Swiss university professors in the early century makes room, particularly in economic sciences, to the rising influence of the USA. This is a sign that an internationalisation of “excellence” has increasingly replaced an internationalisation of “proximity”.